All solid state battery

JP7639391B2Active Publication Date: 2025-03-05TOYOTA JIDOSHA KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021027209
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2025-03-05
Estimated Expiration
2041-02-24

AI Technical Summary

Benefits of technology

【0010】 本開示によれば、負極活物質中で、バインダーの2次粒子の分散径を、所定の分布にすることによって、負極活物質同士、固体電解質同士、あるいは、負極活物質と固体電解質の密着性を向上することができる。そして、この密着性の向上により、充電抵抗が一層低減されている全固体電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639391000002
    Figure 0007639391000002
  • Figure 0007639391000003
    Figure 0007639391000003
  • Figure 0007639391000004
    Figure 0007639391000004
Patent Text Reader

Abstract

To provide an all solid-state battery having charging resistance reduced further more.SOLUTION: An all solid-state battery of the present disclosure includes a negative electrode active material layer containing a negative electrode material, a solid electrolyte and a binder. In the negative electrode active material layer, primary particles of the binder form secondary particles and are dispersed. The binder contains, with respective to the total number of the secondary particles, the secondary particles having a dispersion diameter of 0.05-0.11 μm with a content of 36.8% or more, and also contains the secondary particles having a dispersion diameter of 0.12-0.36 μm with a content of 25.4% or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an all-solid-state battery. In particular, the present disclosure relates to an all-solid-state battery including an anode active material layer containing an anode active material, a solid electrolyte, and a binder. [Background technology]

[0002] In the negative electrode active material layer of an all-solid-state battery, a binder that binds the negative electrode active material, additives, and the like has conventionally been used.

[0003] For example, Patent Document 1 discloses a method for producing an all-solid-state battery, which includes mixing an electrode active material, a binder, a solvent, and the like in a mixer having a stirring blade to obtain granules.

[0004] Patent Document 2 discloses a negative electrode for a non-aqueous electrolyte secondary battery, comprising a first negative electrode active material layer containing graphite as a first negative electrode active material, and a second negative electrode active material layer formed on the first negative electrode active material layer and containing a lithium titanate complex oxide as a second negative electrode active material. Patent Document 2 also discloses that the non-aqueous electrolyte may be a solid electrolyte. Patent Document 2 further discloses that the first negative electrode active material layer and the second negative electrode active material layer contain different types of binders.

[0005] Patent Document 3 discloses an all-solid-state battery in which at least one layer selected from the group consisting of a positive electrode layer, a negative electrode layer, and a solid electrolyte layer contains a particulate first binder and a non-particulate second binder. Patent Document 3 also discloses that the first binder is polyvinylidene fluoride (PVDF), has an average particle size of 0.1 to 130 μm, and is contained in an amount of 0.2 to 7.0 mass%. Patent Document 3 also discloses that the second binder is ethyl cellulose (EC), and is contained in an amount of more than 0 mass% and 1.0 mass% or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-57398 A [Patent Document 2] JP 2012-22794 A [Patent Document 3] JP 2020-194706 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present inventors have found a problem that the reduction in charging resistance is insufficient in the conventional all-solid-state batteries disclosed in Patent Documents 1 to 3 and the like, and that an all-solid-state battery with a further reduced charging resistance is desired.

[0008] The present disclosure has been made to solve the above problems. That is, an object of the present disclosure is to provide an all-solid-state battery with a further reduced charging resistance. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to achieve the above object, and have completed the all-solid-state battery of the present disclosure. The all-solid-state battery of the present disclosure includes the following aspects. That is, one embodiment of the all-solid-state battery of the present disclosure is The negative electrode active material layer includes a negative electrode active material, a solid electrolyte, and a binder. In the negative electrode active material layer, primary particles of the binder form secondary particles and are dispersed, and The binder contains 36.8% or more of the secondary particles having a dispersion diameter of 0.05 to 0.11 μm and 25.4% or less of the secondary particles having a dispersion diameter of 0.12 to 0.36 μm, based on the total number of the secondary particles. It is an all-solid-state battery. Effect of the Invention

[0010] According to the present disclosure, by adjusting the dispersion diameter of the secondary particles of the binder to a predetermined distribution in the negative electrode active material, it is possible to improve the adhesion between the negative electrode active materials, between the solid electrolytes, or between the negative electrode active material and the solid electrolyte. This improvement in adhesion makes it possible to provide an all-solid-state battery with a further reduced charging resistance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is an explanatory diagram showing an example of an FE-SEM image of a cross section of a negative electrode active material layer. [Diagram 2] FIG. 2 is an explanatory diagram showing an example of binarization of the FE-SEM image of FIG. [Diagram 3] FIG. 3 is a graph showing the distribution of dispersed diameters of secondary particles of the binder for each battery sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, embodiments of the all-solid-state battery of the present disclosure will be described in detail. Note that the all-solid-state battery of the present disclosure is not limited to the embodiments described below.

[0013] Without being bound by theory, the reason why the all-solid-state battery of the present disclosure has a further reduced charging resistance compared to conventional all-solid-state batteries will be described.

[0014] The negative electrode active material layer of the all-solid-state battery contains a negative electrode active material, a solid electrolyte, and a binder. In the negative electrode active material layer, binder particles are dispersed. The present inventors have found that if the binder particles are dispersed to a certain degree, the charging resistance of the all-solid-state battery can be further reduced. The present inventors have also found that such a degree of dispersion can be evaluated by the distribution of the dispersed diameter of the secondary particles of the binder.

[0015] Next, the constituent elements of the all-solid-state battery according to the present disclosure, which have been completed based on the findings and the like described above, will be described.

[0016] 《All-solid-state battery》 The all-solid-state battery according to the present disclosure includes a negative electrode active material layer. The negative electrode active material layer will be described below.

[0017] <Negative electrode active material layer> The negative electrode active material layer contains a negative electrode active material, a solid electrolyte, and a binder. Hereinafter, each of the negative electrode active material, the solid electrolyte, and the binder in the negative electrode active material layer will be described.

[0018] <Negative electrode active material> The negative electrode active material can be selected from well-known materials that function as negative electrode active materials for all-solid-state batteries, and is not particularly limited. The negative electrode active material may be selected from materials that can absorb and release metal ions, such as lithium ions. Examples of the negative electrode active material include metallic lithium, lithium alloys, carbon materials such as graphite or hard carbon, silicon materials such as metallic silicon and silicon alloys, and Li4Ti5O 12 (LTO), etc. These materials may be combined and selected. Examples of lithium alloys include LiSn, LiSi, LiAl, LiGe, LiSb, LiP, and LiIn. Metallic lithium means unalloyed lithium. Examples of silicon alloys include alloys with metal elements such as lithium, and may also be alloys with one or more metal elements selected from the group consisting of tin, germanium, and aluminum. Metallic silicon means unalloyed silicon. The negative electrode active material may be selected from other metal materials, such as indium, aluminum, or tin, or a combination thereof. When a graphite material, which is a crystalline carbon material, is selected as the negative electrode active material, the surface of the graphite may be amorphously coated.

[0019] The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape and a thin film shape, and these may be combined. From the viewpoint of ease of handling, a particulate shape is preferred. When the negative electrode active material is particulate, the average particle diameter (D 50) may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 100 μm or less, 50 μm or less, 30 μm or less, 10 μm or less, 1 μm or less, 500 nm or less, 100 nm or less, or 50 nm or less.

[0020] In this specification, unless otherwise specified, the average particle size of particles is the volume-based median diameter (D 50 ) value. Also, the median diameter (D 50 ) is the diameter at which the cumulative volume of particles becomes 50% of the total volume when particles are arranged in order from the smallest particle to the largest particle.

[0021] The content ratio of the negative electrode active material in the negative electrode active material layer is not particularly limited, and may be, for example, 10 mass % or more, 30 mass % or more, 50 mass % or more, 70 mass % or more, or 80 mass % or more, and may be 99 mass % or less, 98 mass % or less, 95 mass % or less, or 90 mass % or less, based on the total mass of the negative electrode active material layer.

[0022] <Solid electrolyte> Examples of the solid electrolyte include sulfide-based amorphous solid electrolytes, such as Li2S-P2S5, Li2O·Li2S·P2S5, Li2S, P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-LiBr-Li2S-P2S5, and LiI-Li3PO4-P2S5; or oxide-based amorphous solid electrolytes, such as Li2O-B2O3-P2O 5、 Li2O-SiO2, etc.; or oxide-based crystalline solid electrolytes, such as LiI, Li3N, Li5La3Ta2O 12 , Li7Zr2O 12 , Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) N w (w<1), etc.; or sulfide-based crystalline solid electrolytes, such as Li7P3S 11 , Li 3.25 P 0.75 Glass ceramics such as S4, or Li 3.24 P0.24 Ge 0.76 S4 or other thio-LiSiO-based crystals, Li6PS5X (X=Cl, Br) or other crystals having an argyrodite-type crystal structure (hereinafter sometimes referred to as "argyrodite-type sulfide solid electrolytes"); or a combination thereof. From the viewpoint of high lithium ion conductivity and electrochemical stability, argyrodite-type sulfide solid electrolytes are preferred.

[0023] The shape of the solid electrolyte is not particularly limited, but from the viewpoint of ease of handling, a particulate form is preferred. When the solid electrolyte is particulate, its average particle size (D 50 ) may be 0.1 μm or more, 0.3 μm or more, or 0.5 μm or more, and may be 5 μm or less, 4 μm or less, 3 μm or less, 2 μm or less, or 1 μm or less.

[0024] <binder> There is no particular restriction on the binder as long as it can be dispersed in the negative electrode active material layer with a predetermined dispersion diameter. The binder may typically be one or more resins selected from the group consisting of fluorine-based resins and polyolefin-based resins, but is not limited thereto. From the viewpoint of facilitating obtaining a predetermined dispersion diameter, fluorine-based resins, particularly polyvinylidene fluoride (PVDF), are preferred. Examples of fluorine-based resins include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), perfluoroalkoxyalkane (PFA), and the like. These may be selected in combination. Examples of polyolefin-based resins include styrene butadiene rubber (SBR), polypropylene (PP), polyethylene (PE), and (meth)acrylic resins such as polymethyl methacrylate (PMMA), polymethyl acrylate, polybutyl acrylate (PBA), and polyacrylonitrile (PAN). These may be selected in combination.

[0025] In the negative electrode active material layer, the primary particles of the binder form secondary particles and are dispersed. If the distribution of the dispersion diameter of the secondary particles of the binder is as follows, the adhesion between the negative electrode active materials, between the solid electrolytes, or between the negative electrode active material and the solid electrolyte is improved. The charging resistance of an all-solid-state battery including a negative electrode active material layer having such good adhesion is further reduced.

[0026] The above-mentioned adhesion is improved when the binder contains 36.8% or more, 37.0% or more, 38.0% or more, or 39.0% or more of secondary particles having a dispersion diameter of 0.05 to 0.11 μm relative to the total number of secondary particles, and 25.4 or less, 25.0% or less, 24.0% or less, 23.0% or less, or 22.0 or less of secondary particles having a dispersion diameter of 0.12 to 0.36 μm. The upper limit of the existence ratio of secondary particles having a dispersion diameter of 0.05 to 0.11 μm is not particularly limited, but is preferably 70.0%, 60.0%, 50.0%, 40.0%, or 39.7% relative to the total number of secondary particles of the binder. In addition, the proportion of secondary particles having a dispersion diameter of 0.12 to 0.36 μm is preferably as low as possible, but it does not have to be 0%, and there is no practical problem even if the lower limit is 1.0%, 5.0%, 10.0%, 15.0%, 20.0%, or 21.0%. m The proportion of secondary particles having a dispersion diameter of more than 0.36 μm is preferably as low as possible, and may be 5% or less, 3% or less, or 1%, and ideally 0%, but preferably 0.36 μm or less. m If the proportion of secondary particles having a dispersion diameter of more than 0.5%, this is practically acceptable.

[0027] The distribution of the dispersed diameters of the secondary particles of the binder can be obtained as follows.

[0028] The secondary particle components of the binder are surface-analyzed on the cross section of the negative electrode active material layer, and the frequency distribution of the maximum length of each region of the secondary particles recognized by the surface analysis is obtained, thereby obtaining the distribution of the dispersion diameter of the secondary particles of the binder.

[0029] For example, when the binder is a fluororesin, the distribution of secondary particles of the binder is obtained, for example, as follows. In an inert atmosphere, the exterior member such as a laminate of the all-solid-state battery is peeled off, and the electrode is taken out. While maintaining the inert atmosphere, the electrode is cut to an appropriate size, and then the cross section of the electrode is processed in a vacuum or in an inert atmosphere, for example, using an ion milling device. At that time, the cross section of the electrode is processed while being cooled so that the binder and the like do not deteriorate. For the electrode after the cross section processing, a secondary electron image and a backscattered electron image are obtained in a vacuum using an FE-SEM, and further, an EDX surface analysis is performed for fluorine (F). For the EDX surface analysis result, a binarized image processing is performed so that the area where the secondary particles of the binder exist can be visually distinguished from the other areas. The binarization threshold is appropriately determined with reference to the binder content ratio in the negative electrode active material layer. From the binarized image, the number of pixels in the area where the secondary particles of the binder exist is counted, and the frequency distribution of the maximum length of the secondary particles of the binder is obtained. The maximum length of the secondary particles of the binder is calculated from the magnification of the secondary electron image and the backscattered electron image.

[0030] The content ratio of the binder in the negative electrode active material layer may be appropriately determined in consideration of the binding strength, etc., so as to obtain the above-mentioned distribution of the dispersion diameter. The content ratio of the binder in the negative electrode active material layer may be, for example, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.7 mass% or more, 1.0 mass% or more, 2.0 mass% or more, or 3.0 mass% or more, and may be 8.0 mass% or less, 7.0 mass% or less, or 5.0 mass% or less, based on the total mass of the negative electrode active material layer.

[0031] As long as the dispersion diameter of the secondary particles of the binder does not become the above-mentioned distribution, the negative electrode active material layer may optionally contain, for example, a solvent for the binder, a conductive material, and the like.

[0032] <Binder Solvent> The binder solvent is not particularly limited as long as it can achieve the above-mentioned distribution of dispersion diameters of secondary particles of the binder. Examples of the binder solvent include butyl butyrate, toluene, and methyl ethyl ketone (MEK), and may be a mixed solvent of these. From the viewpoint of easily achieving the above-mentioned distribution of dispersion diameters of secondary particles, butyl butyrate is preferred as the binder solvent.

[0033] <Conductive material> The conductive material may be selected from carbon materials such as VGCF (Vapor Grown Carbon Fiber), acetylene black, Ketjen black, carbon nanotubes, or the like, or a combination thereof.

[0034] The all-solid-state battery of the present disclosure may include a known anode current collector, a solid electrolyte layer, a cathode active material layer, and a cathode current collector layer in addition to the above-mentioned anode active material layer. The all-solid-state battery of the present disclosure may include the anode current collector, the anode active material layer, the solid electrolyte layer, the cathode active material layer, and the cathode current collector in this order. Below, the anode current collector, the solid electrolyte layer, the cathode active material layer, and the cathode current collector layer will be generally described, but are not limited thereto.

[0035] <Negative electrode current collector> As the negative electrode current collector, for example, Ag, Cu, Au, Al, Ni, Fe, stainless steel, Ti, or alloys thereof can be used as the material of the negative electrode current collector layer. From the viewpoint of chemical stability, Cu and Ni are preferred, and when a sulfide-based solid electrolyte is used, Ni is particularly preferred from the viewpoint of avoiding sulfurization of the negative electrode current collector.

[0036] <Solid electrolyte layer> The solid electrolyte layer contains at least a solid electrolyte, and may optionally contain a binder and the like.

[0037] Examples of the solid electrolyte used in the solid electrolyte layer include the solid electrolytes described in "<Negative electrode active material layer>". The content of the solid electrolyte in the solid electrolyte layer is not particularly limited, and may be, for example, 50 mass% or more, 70 mass% or more, or 90 mass% or more, and 99.9 mass% or less, 98 mass% or less, or 95 mass% or less, based on the total mass of the solid electrolyte layer.

[0038] Examples of binders include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), butylene rubber (BR), styrene-butadiene rubber (SBR), polyvinyl butyral (PVB), acrylic resin, etc. These may be used in combination. Also, heptane, etc., may be used as a solvent for these binders.

[0039] The content ratio of the binder in the solid electrolyte layer may be appropriately determined in consideration of the binding strength, etc. The content ratio of the binder in the solid electrolyte layer may be, for example, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.7 mass% or more, 1.0 mass% or more, 2.0 mass% or more, or 3.0 mass% or more based on the total mass of the solid electrolyte layer, and may be 8.0 mass% or less, 7.0 mass% or less, or 5.0 mass% or less.

[0040] <Cathode active material layer> The positive electrode active material layer contains a positive electrode active material, and optionally a conductive material, a binder, and a solid electrolyte. The positive electrode active material can be selected from metal oxides containing lithium and at least one transition metal selected from manganese, cobalt, nickel, and titanium, such as lithium cobalt oxide, lithium nickel oxide, lithium manganate, or lithium nickel cobalt manganate, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, or a combination thereof.

[0041] The shape of the positive electrode active material is not particularly limited, and examples thereof include a particulate shape and a thin film shape, and these may be combined. From the viewpoint of ease of handling, a particulate shape is preferred. When the positive electrode active material is particulate, the average particle diameter (D 50 ) may be 1 nm or more, 5 nm or more, or 10 nm or more, and may be 100 μm or less, 50 μm or less, 30 μm or less, 10 μm or less, 1 μm or less, 500 nm or less, 100 nm or less, or 50 nm or less.

[0042] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material. This can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. These may be used in combination. The thickness of the coating layer may be, for example, 0.1 nm or more, 1 nm or more, or 10 nm or more, and may be 100 nm or less, 50 nm or less, or 20 nm or less.

[0043] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, and may be, for example, 10 mass % or more, 30 mass % or more, 50 mass % or more, 70 mass % or more, or 80 mass % or more, and may be 99 mass % or less, 98 mass % or less, 95 mass % or less, or 90 mass % or less, based on the total mass of the positive electrode active material layer.

[0044] The conductive material may be the conductive material described in "<Negative electrode active material layer>". The solid electrolyte may be the solid electrolyte described in "<Negative electrode active material layer>". In addition, the binder and its solvent may be the binder and its solvent described in "<Solid electrolyte layer>".

[0045] <Positive electrode current collector> For the positive electrode current collector, reference can be made to the negative electrode current collector described in “<Negative electrode current collector>.” Among them, aluminum is preferred as the positive electrode current collector from the viewpoint of chemical stability.

[0046] 《Manufacturing method》 The manufacturing method of the all-solid-state battery of the present disclosure is not particularly limited as long as the negative electrode active material layer can be formed so that the dispersion diameter of the secondary particles of the binder in the negative electrode active material layer is distributed as described above. In order to form such a negative electrode active material layer, without being bound by theory, when the negative electrode active material, the binder, and the binder solvent are mixed to prepare the binder dispersion, if they are mixed at room temperature, they are stirred while breaking up the aggregation of the primary particles of the binder. Also, without being bound by theory, when the negative electrode active material, the binder, and the binder solvent are mixed at a high temperature to prepare the binder dispersion, the aggregation force of the primary particles of the binder is small, so it is sufficient to simply stir them. The high temperature is 30°C or higher and a temperature at which the binder and the binder solvent do not decompose. Such a temperature may be, for example, 30°C or higher, 40°C or higher, 50°C or higher, or 60°C or higher, and may be 100°C or lower, 90°C or lower, or 70°C or lower. In the dispersion liquid prepared in this manner, the secondary particles of the binder are less likely to become coarse, and the binder is uniformly dispersed in the dispersion liquid.

[0047] Examples of the method of stirring while breaking up the aggregation of the primary particles of the binder include a method using a mixer with a rotating blade and an ultrasonic homogenizer. These methods may be combined. Examples of the method of simply stirring include a method using a stirrer.

[0048] At least a solid electrolyte is added to the binder dispersion liquid thus obtained to prepare a negative electrode mixture paste, and the negative electrode mixture paste is used to form a negative electrode active material layer. A conductive material and a solvent for the binder may be further added to the negative electrode mixture. The conductive material and the solvent for the binder may be the materials described in "Negative electrode active material layer". Examples of methods for forming the negative electrode active material layer include, but are not limited to, a method of applying a negative electrode mixture paste to the surface of a negative electrode current collector and drying it.

[0049] The method for applying the negative electrode mixture paste to the surface of the negative electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. These methods may be used in combination.

[0050] The formation of the solid electrolyte layer, the positive electrode active material layer, and the power generating element (single cell), and the lamination of the power generating element (single cell) can be performed by using a well-known manufacturing method for all-solid-state batteries. The formation of the solid electrolyte layer, the positive electrode active material layer, and the power generating element (single cell), and the lamination of the power generating element (single cell) will be outlined below, but the method is not limited thereto.

[0051] The method for forming the solid electrolyte layer is not particularly limited, and a well-known method can be used. For example, a method of compressing and molding a powder or pellet of a raw material for forming a solid electrolyte layer containing at least a solid electrolyte, etc., can be mentioned. Alternatively, a method of applying a raw material paste for forming a solid electrolyte layer containing at least a solid electrolyte and a solvent to the surface of a support and drying it can be mentioned.

[0052] The method for forming the positive electrode active material layer is not particularly limited. For example, a method of applying a positive electrode mixture paste containing at least a positive electrode active material to the surface of a positive electrode current collector and drying the paste can be mentioned. The method of applying the positive electrode mixture paste to the surface of a positive electrode current collector can refer to the method of applying the negative electrode mixture paste to the surface of a negative electrode current collector.

[0053] A negative electrode current collector, a negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector are laminated in this order to form a power generating element (single cell). There is no particular limitation on the lamination method. For example, a solid electrolyte layer is formed on the surface of a support, and the solid electrolyte layer side is bonded to one of the negative electrode active material layer and the positive electrode active material layer, and pressed. Thereafter, the support of the solid electrolyte layer is peeled off, and the other of the negative electrode active material layer and the positive electrode active material layer is bonded to the surface of the solid electrolyte layer, and pressed again. A roll press or the like may be used for pressing.

[0054] Furthermore, the power generating elements (single cells) may be stacked. When the power generating elements (single cells) are stacked, the positive and negative electrode current collectors may not be attached to each of the single cells, and the positive and negative electrode current collectors may be attached to both ends of the stack. After stacking the power generating elements (single cells), they may be pressed, and a roll press or the like may be used for pressing.

[0055] Transformation In addition to the above, the all-solid-state battery of the present disclosure may be modified in various ways within the scope of the claims. For example, the all-solid-state battery of the present disclosure may include an exterior body that houses a negative electrode collector, a negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode collector layer. The shape of the exterior body is not particularly limited, and examples thereof include a laminate type. The material of the exterior body is not particularly limited as long as it is stable against the solid electrolyte, and examples thereof include resins such as polypropylene, polyethylene, and acrylic resin. These may be used in combination. EXAMPLES

[0056] The all-solid-state battery of the present disclosure will be described in more detail below with reference to examples and comparative examples. Note that the all-solid-state battery of the present disclosure is not limited to the conditions used in the following examples.

[0057] <Preparation of battery samples> A battery sample was prepared as follows.

[0058] Example 1 Preparation of binder dispersion Butyl butyrate as a solvent and PVDF powder as a particulate binder were mixed in a mass ratio of 95:5. At this time, butyl butyrate was kept at room temperature of 30°C or less, and PVDF powder was added while stirring, and this was stirred using a stirrer for more than one hour. After that, the binder particles were dispersed for 30 minutes using an ultrasonic homogenizer (SUH-50 manufactured by MST Corporation). This resulted in a binder dispersion in which the binder particles were dispersed in the solvent.

[0059] -Preparation of negative electrode mixture paste The negative electrode active material is Li4Ti5O with an average primary particle size of 0.7 μm. 12 1.0 g of the particles, 0.025 g of VGCF (conductive carbon), 1.042 g of binder dispersion, and 1.6 g of butyl butyrate were weighed and mixed for 30 minutes using an ultrasonic homogenizer (UH-50, manufactured by MST Corporation). Then, 1.336 g of solid electrolyte was added to the slurry obtained by mixing, and the mixture was mixed again for 30 minutes using an ultrasonic homogenizer (UH-50, manufactured by MST Corporation) to obtain a negative electrode mixture paste.

[0060] ·Preparation of positive electrode mixture paste The positive electrode active material is lithium nickel cobalt manganese oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A LiNbO3 coating layer was formed on the positive electrode active material. 2.0 g of this positive electrode active material, 0.048 g of conductive carbon VGCF, 0.407 g of solid electrolyte, 0.016 g of PVDF, and 1.3 g of butyl butyrate were weighed and mixed using an ultrasonic homogenizer (UH-50 manufactured by MST Corporation) to obtain a positive electrode mixture paste.

[0061] ·Preparation of paste for forming solid electrolyte layer A heptane solution containing heptane and 5% by mass of a butadiene rubber binder, and LiI-LiBr-Li2S-P2S5-based glass ceramics having an average particle size of 2.5 μm as a solid electrolyte were charged into a polypropylene container. Then, this was mixed for 30 seconds using an ultrasonic homogenizer (UH-50 manufactured by MST Corporation). Next, the polypropylene container was shaken for 3 minutes using a shaker to obtain a paste for a solid electrolyte layer.

[0062] Preparation of negative and positive electrode active material layers The negative electrode mixture paste was applied to the surface of the negative electrode current collector by the blade method using an applicator, and this was dried on a hot plate at 100 ° C for 30 minutes to form a negative electrode active material layer on the surface of the aluminum foil. In the same manner, the positive electrode mixture paste was applied to the surface of the positive electrode current collector (aluminum foil) and dried to obtain a positive electrode active material layer. The basis weight of the negative electrode mixture was adjusted so that the negative electrode capacity charge specific capacity was 1.15 times when the positive electrode charge specific capacity was 185 mAh / g.

[0063] Preparation of the solid electrolyte layer The negative electrode active material layer (negative electrode) formed on the surface of the negative electrode current collector was pressed in advance. A paste for a solid electrolyte layer was applied to the surface of the negative electrode on the negative electrode active material layer side after pressing using a die coater, and the paste was dried for 30 minutes on a hot plate at 100°C. Then, a pressure of 2 ton / cm was applied. 2 The laminate was then roll-pressed at 800° C. to obtain a negative electrode-side laminate having a solid electrolyte layer on the surface of the negative electrode.

[0064] Similarly, the positive electrode active material layer (positive electrode) formed on the surface of the positive electrode current collector was pressed in advance. The paste for the solid electrolyte layer was applied to the surface of the positive electrode active material layer side of the pressed positive electrode using a die coater, and dried for 30 minutes on a hot plate at 100°C. Then, the paste was dried at 2 ton / cm 2 The laminate was then roll-pressed at 800° C. to obtain a positive electrode-side laminate having a solid electrolyte layer on the surface of the positive electrode.

[0065] -Preparation of power generation elements The positive electrode side laminate and the negative electrode side laminate were punched out, and the solid electrolyte layers were laminated together. Here, the positive electrode side laminate and the negative electrode side laminate were laminated in a state in which an unpressed solid electrolyte layer (solid electrolyte layer paste) was transferred between the solid electrolyte layer of the positive electrode side laminate and the solid electrolyte layer of the negative electrode side laminate. Then, the laminate was heated at 130° C. with a pressure of 2 ton / cm. 2 The battery sample of Example 1 was obtained by pressing the negative electrode current collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode current collector in this order. The power generating element was sealed with a laminate and restrained at 5 MPa.

[0066] Example 2 Butyl butyrate as a solvent and PVDF powder as a particulate binder were mixed in a mass ratio of 95:5. At this time, butyl butyrate was kept at a high temperature of 40°C, and PVDF powder was added while stirring, and this was stirred using a stirrer for more than 1 hour. In this way, a battery sample of Example 2 was obtained in the same manner as in Example 1, except that a binder dispersion in which binder particles were dispersed in a solvent was obtained.

[0067] Example 3 Butyl butyrate as a solvent and PVDF powder as a particulate binder were mixed in a mass ratio of 95:5. At this time, butyl butyrate was kept at room temperature of 30°C or less, and PVDF powder was added while stirring, and this was stirred using a stirrer for more than 1 hour. After that, the binder particles were dispersed for 30 minutes using FILMICS (30-L type manufactured by Primix Corporation). As a result, a battery sample of Example 3 was obtained in the same manner as Example 1, except that a binder dispersion in which the binder particles were dispersed in the solvent was obtained. FILMICS (30-L type manufactured by Primix Corporation) is a mixer having a rotating blade.

[0068] Comparative Example 1 Butyl butyrate as a solvent and PVDF powder as a particulate binder were mixed in a mass ratio of 95:5. At this time, the butyl butyrate was kept at room temperature of 30 or less, the PVDF powder was added while stirring, and this was stirred with a stirrer for 1 hour or more to obtain a binder dispersion liquid. A battery sample of Comparative Example 1 was obtained in the same manner as in Example 1.

[0069] "evaluation" Each battery sample was charged at a constant current equivalent to 1C, and after the cell voltage reached 2.95 V, it was charged at a constant voltage, and charging was terminated when the charging current reached 0.01 C. In addition, each battery sample after charging was discharged at a constant current equivalent to 1C, and discharging was terminated when the cell voltage reached 1.5 V. Then, it was charged at a constant current equivalent to 3C, and the difference between the voltage before charging and the voltage after 10 seconds of charging was divided by the current equivalent to 3C to calculate the 10 seconds DC resistance (charging resistance).

[0070] In addition, the secondary particle dispersion diameter of the binder in the negative electrode active material layer of each battery sample was determined by the method described in "Negative electrode active material layer". An ion milling device (IM4000PLUS) manufactured by Hitachi High-Technologies Corporation was used to process the cross section of the electrode. A secondary electron image and a backscattered electron image of the processed cross section of each battery sample were obtained using an FE-SEM device (Regulus SU8230) manufactured by Hitachi High-Technologies Corporation. The observation magnification was 1000 times. FIG. 1 is an explanatory diagram showing an example of an FE-SEM image of the cross section of the negative electrode active material layer. FIG. 2 is an explanatory diagram showing an example of binarization of the FE-SEM image of FIG. 1. In FIG. 2, the dark field indicates the region of the secondary particles of the binder. FIG. 3 is a graph showing the distribution of the dispersion diameter of the secondary particles of the binder for each battery sample.

[0071] The results are shown in Table 1. Table 1 also shows the method for producing the binder dispersion used to produce the negative electrode mixture paste.

[0072] [Table 1]

[0073] From Table 1 and FIG. 3, the following can be understood regarding the binder in the obtained negative electrode active material layer.

[0074] It can be seen that when stirring with a stirrer and then further stirring with an ultrasonic homogenizer or a mixer having a rotating blade is performed at room temperature, the proportion of secondary particles with a large dispersion diameter is reduced (Examples 1 and 3). It can also be seen that when stirring with a stirrer is performed at a high temperature (40°C), the proportion of secondary particles with a large dispersion diameter is reduced even without further stirring with an ultrasonic homogenizer or a mixer having a rotating blade (Filmix) (Example 2). It can also be seen that the charging resistance is reduced in the battery samples (all-solid-state batteries) having the negative electrode active material layers of Examples 1 to 3 in which the dispersion diameters of the binder secondary particles show such a distribution.

[0075] On the other hand, when stirring with a stirrer is performed at room temperature, and then without further stirring with an ultrasonic homogenizer or a mixer (Filmix) having a rotating blade, it can be seen that the proportion of secondary particles with a large dispersion diameter is high (Comparative Example 1).And, it can be seen that the charge resistance is high in the battery sample (all-solid-state battery) having the negative electrode active material layer of Comparative Example 1 in which the dispersion diameter of the binder secondary particles shows such a distribution.

[0076] From the above results, the effects of the all-solid-state battery according to the present disclosure were confirmed.

Claims

1. The negative electrode active material layer includes a negative electrode active material, a solid electrolyte, and a binder. In the negative electrode active material layer, primary particles of the binder are dispersed while forming secondary particles, and The binder is a type of resin, The binder contains 36.8% or more of the secondary particles having a dispersion diameter of 0.05 to 0.11 μm, 25.4% or less of the secondary particles having a dispersion diameter of 0.12 to 0.36 μm, and 5% or less of the secondary particles having a dispersion diameter of more than 0.36 μm, relative to the total number of the secondary particles. All-solid-state battery.

2. The all-solid-state battery as described in claim 1, wherein the binder is polyvinylidene fluoride.

Citation Information

Patent Citations

  • Negative electrode for nonaqueous secondary battery

    JP2010182626A

  • Negative electrode for nonaqueous electrolyte secondary battery, and method of manufacturing the same

    JP2011065929A

  • Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2012022794A

  • Manufacturing method of electrode

    JP2019057398A

  • All-solid battery and manufacturing method thereof

    JP2020194706A